2013
DOI: 10.1111/aji.12141
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Anti‐HLA Antibodies in Maternal Blood in the Second Trimester to Identify Patients at Risk of Antibody‐Mediated Maternal Anti‐Fetal Rejection and Spontaneous Preterm Delivery

Abstract: Problem Maternal anti-fetal rejection is a mechanism of disease in spontaneous preterm labor. The objective of this study was to determine whether the presence of human leukocyte antigen (HLA) panel-reactive antibodies (PRA) during the second trimester increases the risk for spontaneous preterm delivery. Methods of Study This longitudinal case-control study included pregnant women with spontaneous preterm deliveries (n=310) and control patients with normal term pregnancies (n=620), matched for maternal age a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 143 publications
3
32
0
Order By: Relevance
“…In melanoma patients, detectable levels of sHLA-DR in serum appeared only in the later stage of the disease. The above findings on the increased level of sHLA-DR in sera of patients with ALL were confirmed by Thompson, et al [163], using a double-determinant ELISA with two mAbs. They further compared sHLA-II in the blood of healthy people and of patients who received either an allogeneic or autologous bone-marrow transplant.…”
Section: Soluble Hla-ii In Serumsupporting
confidence: 54%
“…In melanoma patients, detectable levels of sHLA-DR in serum appeared only in the later stage of the disease. The above findings on the increased level of sHLA-DR in sera of patients with ALL were confirmed by Thompson, et al [163], using a double-determinant ELISA with two mAbs. They further compared sHLA-II in the blood of healthy people and of patients who received either an allogeneic or autologous bone-marrow transplant.…”
Section: Soluble Hla-ii In Serumsupporting
confidence: 54%
“…Other studies have found increased maternal serum HLA class I (classic) antibodies to be associated with spontaneous PTB and fetal inflammatory responses, suggesting a component of maternal-anti-fetal rejection in the pathogenesis of PTB[33,34]. Thus, our finding that non-classic (immuno-tolerant) HLA protein is higher on fetally derived cells from PTB than from term birth suggests that maternal-fetal interactions may jointly contribute to pregnancy tolerance or rejection[33,34].…”
Section: Discussionmentioning
confidence: 99%
“…Chronic chorioamnionitis, the most common placental lesion in late spontaneous preterm birth, which is characterized by maternal T-cell infiltration of the chorion laeve with trophoblast apoptosis, resembles allograft rejection ( 44 ). Maternal sensitization to fetal HLAs is frequently found in patients with chronic chorioamnionitis, and is accompanied by complement deposition in umbilical vein endothelium ( 45, 46 ). A novel form of fetal systemic inflammation characterized by overexpression of T-cell chemokines ( e.g.…”
Section: Preterm Labor As a Syndrome Associated With Multiple Mechanimentioning
confidence: 99%